Determinan Voluntary Disclosure Level: Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Dwi Putra Oktaviani (Department of Accounting-Faculty of Economic and Business (FEB), 2016)
This research is aimed to examine the effect of controlling ownership proxied by entrenchment effect and alignment effect, agency problem proxied by free cash flow, and independent board commissioner toward the firm’s voluntary disclosure level. This research used the sample of manufacture industries which listed in Indonesian Stock Exchange during 2014-2015 periods .Based on purposive sampling method, the number of manufacture industries sampled in this study 86 companies with 2 years observation., the total amount of sample obtained in this research were 172 samples. This research used multiple linear regression analysis method. The results of the analysis in this research showed that entrenchment effect and alignment effect effected and negative towardthefirm’s voluntary disclosure level and find that independent board commissioner effected and positive toward the firm’s voluntary disclosure level. Whilefree cash flow did not effect on the firm’s voluntary disclosure level